J.K Rowling Harry potter and the Chamber of Sectets - Tally T Robert (London Bloomsbury, 1998)
This book is a critical introduction to J.R.R. Tolkiens The Hobbit, but it also advances an argument about the novel in the context of Tolkiens larger literary and philosophical project. Notwithstanding its canonical place in the fantasy genre, The Hobbit is ultimately a historical novel. It does not refer directly to any "real" historical events, but it both enacts and conceptualizes history in a way that makes it real. Drawing on Marxist literary criticism and narrative theory, this book examines the form and content of Tolkiens work, demonstrating how the heroic romance is simultaneously employed and subverted by Tolkien in his tale of an unlikely hero, "quite a little fellow in a wide world," who nonetheless makes history. First-time readers of Tolkien, as well as established scholars and fans, will enjoy this engaging and accessible study of The Hobbit. Robert T. Tally Jr. is a Professor of English at Texas State University, USA. His books include For a Ruthless Critique of All That Exists: Literature in an Age of Capitalist Realism (2022), Topophrenia: Place, Narrative, and the Spatial Imagination (2019), and Fredric Jameson: The Project of Dialectical Criticism (2014)